Quality of some hybrid seeds of rice and control of seed borne fungi in Bangladesh - Akter, MA; Hossain, I (Journal of the Bangladesh Agricultural University, 2016)
A study was conducted for assessing quality of 15 hybrid rice seed samples and management of seed borne fungal pathogens by three selected chemicals namely Bavistin (0.3%), Thiovit (0.3%) and Provax (0.3%) along with two botanicals such as: Garlic extract (Allium sativum) (1:1) and Allamanda leaf extract (Allamanda cathartica) (1:1) and a bio-control agent BAU-Biofungicide @ 3% (Trichoderma based preparation) at Seed Pathology Centre, MS Laboratory and Eco-friendly Plant Disease Management Laboratory of Department of Plant Pathology, Bangladesh Agricultural University, Mymensingh during 2013-14. Collected seed samples were categorized by dry inspection as apparently healthy seed (35.7 to 85.7%), discolored seed (0.5 to 22.2%), spotted seed (0.7 to 8.1%), broken seed (0.4 to 44.3%), deformed seed (0 to 1.4%), insect damaged seed (0 to 4.9%), chaffy seed (0 to 1.1%), varietal mixture (0 to 7.2%) and inert matter (0 to 2.6%). In case of purity analysis, pure seed ranged from 92.86 to 100.00%, other seeds 0 to 7.14% and inert matter 0 to 2.59%. 100% pure seed was recorded in Agomoni, Jagoron, Gold, Suborno, Hira-1, Hira-2, Hira-4 and Hira-6 collected from Ispahani Agro. Ltd., BRAC, Lal Teer seed Co. Ltd. and Supreme seed Co. Ltd. Seed treatment with Allamanda leaf extract, Provax and BAU-Biofungicide increased germination, Vigor index and decreased prevalence of seed borne fungi. Among the treatments, biofungicide increased germination 54.39% in blotter method and 89.58% in tray method over control. In addition, BAU-Biofungicide increased up to 713.78% vigor index over untreated control. BAU-Biofungicide may be recommended for controlling seed borne fungal pathogens of hybrid rice in Bangladesh. J. Bangladesh Agril. Univ. 13(2): 161-168, December 2015